2013
DOI: 10.1038/ncomms3478
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation and priming by topoisomerase IIα in embryonic stem cells

Abstract: Topoisomerases resolve torsional stress, while their function in gene regulation, especially during cellular differentiation, remains unknown. Here we find that the expression of topo II isoforms, topoisomerase IIa and topoisomerase IIb, is the characteristic of dividing and postmitotic tissues, respectively. In embryonic stem cells, topoisomerase IIa preferentially occupies active gene promoters. Topoisomerase IIa inhibition compromises genomic integrity, which results in epigenetic changes, altered kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
75
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 59 publications
13
75
0
Order By: Relevance
“…Previous studies, including our own work, have revealed highly synchronous and reproducible changes in the epigenome and transcriptome during neuronal differentiation in this system that were also in good agreement with mouse primary cortical neurons ( Fig. 1A,B; Mohn et al 2008;Lienert et al 2011;Stadler et al 2011;Tiwari et al 2012a,b;Thakurela et al 2013). We performed the FAIRE assay at three distinct time points during neuronal differentiation: NP, TN day 1 (TND1) (immediate/early neurons, marking onset of neurogenesis), and TN day 10 (TND10) (late neurons, representing terminally differentiated postmitotic neurons) and subjected the derived material to high-throughput sequencing (FAIRE-seq) (Supplemental Fig.…”
Section: Faire-seq Sensitively Identifies Accessible Chromatin Duringsupporting
confidence: 65%
“…Previous studies, including our own work, have revealed highly synchronous and reproducible changes in the epigenome and transcriptome during neuronal differentiation in this system that were also in good agreement with mouse primary cortical neurons ( Fig. 1A,B; Mohn et al 2008;Lienert et al 2011;Stadler et al 2011;Tiwari et al 2012a,b;Thakurela et al 2013). We performed the FAIRE assay at three distinct time points during neuronal differentiation: NP, TN day 1 (TND1) (immediate/early neurons, marking onset of neurogenesis), and TN day 10 (TND10) (late neurons, representing terminally differentiated postmitotic neurons) and subjected the derived material to high-throughput sequencing (FAIRE-seq) (Supplemental Fig.…”
Section: Faire-seq Sensitively Identifies Accessible Chromatin Duringsupporting
confidence: 65%
“…The discoveries of TOP2A in the Pol II complex and TOP2A requirement for chromatin dependent in vitro transcription (Mondal and Parvin 2001) are in concert with this conclusion, as are the enriched TOP2 binding in highly transcribed Saccharomyces cerevisiae genes (Sperling et al 2011) and the reduced expression of longer genes with yeast Top2 inhibition (Joshi et al 2012). Although murine ES cells display TOP2A binding at promoters (Thakurela et al 2013), we do not find TOP2A CCR enrichment at promoters. Because TOP2A binding does not necessarily equate to cleavage (Mueller-Planitz and Herschlag 2007; Lee et al 2012), our study and the mouse ES cell study together suggest that TOP2A begins to track supercoil accumulation starting at the promoter but then cleaves well into the gene body during transcription elongation.…”
Section: Discussionmentioning
confidence: 56%
“…TOP2A was identified in the Pol II complex (Mondal and Parvin 2001). A switch from TOP2A to TOP2B binding at promoters of long genes during neuronal differentiation (Tiwari et al 2012;Thakurela et al 2013) suggested promoter priming by TOP2A for murine ES cell differentiation (Thakurela et al 2013).…”
mentioning
confidence: 99%
“…TOP2A and TOP2B are not functionally redundant despite their structural and catalytic similarities [6]. TOP2A is expressed in proliferating cells [7, 8] and knocking out Top2a in mice leads to defects in nuclear division and early embryonic lethality [911]. In contrast, TOP2B is ubiquitously expressed and is upregulated during cellular differentiation [7].…”
Section: Introductionmentioning
confidence: 99%